THE APPLICATION OF STUDENTS TEAM ACHIEVEMENT DIVISION TECHNIQUE TO IMPROVE STUDENTS' READING SKILL IN NARRATIVE TEXT - Kadir, Siska; Miolo, Sartin; Malabar, Fahria (Jurnal Bahasa, Sastra, dan Budaya, 2024)
This study aims to determine whether the application of the Student Team Achievement Division (STAD) technique can improve students' reading skills in narrative texts. The study sampled 30 students from class IX-4 of SMPN 4 Gorontalo. To collect data, a multiple-choice test was used adapted from various fairy tale stories, including "Why Frogs and Mosquitoes are Enemies," "Unhelpful Friends," "The Hungry Mouse," "The Lion and the Mouse," "A Proud Tiger," and "A Cat and a Fox." The study employed a pre-experimental design with one group pre-test and post-test. Results show that the mean score of the pre-test was 14.47, while the mean score of the post-test was 19.4. The hypothesis testing revealed that tcount â‰¥ tlist with a value of 18.84 2.048, indicating that the research hypothesis (H1) is accepted. Therefore, it can be concluded that the Student Team Achievement Division (STAD) technique can improve the reading skills of class IX-4 students at SMP N 4 Gorontalo.